2019
DOI: 10.19126/suje.455536
|View full text |Cite
|
Sign up to set email alerts
|

Futbol Hakemlerinin Öz-Yeterlik Düzeylerinin İncelenmesi

Abstract: In this study, we aimed to examine the self-efficacy levels of soccer referees in the context of some demographic variables (gender, education level, age of starting refereeing, and ocupation). The study group consisted of a total of 154 soccer referees during the 2017-2018 football season of whom 33 (21.4%) were females and 121 (78.6%) were males from different regions and classifications ( X age = 26.87±1.966). The personal information form and the Referee Self-Efficacy Scale (REFS) were used as data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
1
2
1
Order By: Relevance
“…The results of the analysis also showed that a higher level of education in international volleyball referees was significantly associated with higher levels on all four dimensions of referees’ self-efficacy. This result does not agree with the findings of Karaçam et al [ 13 ], who did not find any association between education and self-efficacy in basketball referees; however, it is in line with the results of a study on football referees determining that the level of self-efficacy and game knowledge of the football referees with a bachelor’s degree was higher than that of football referees with high school degree [ 15 ].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…The results of the analysis also showed that a higher level of education in international volleyball referees was significantly associated with higher levels on all four dimensions of referees’ self-efficacy. This result does not agree with the findings of Karaçam et al [ 13 ], who did not find any association between education and self-efficacy in basketball referees; however, it is in line with the results of a study on football referees determining that the level of self-efficacy and game knowledge of the football referees with a bachelor’s degree was higher than that of football referees with high school degree [ 15 ].…”
Section: Discussioncontrasting
confidence: 85%
“…According to Dereceli et al [15], the years of experience increase decision-making ability, but this is not evident in our analysis. Our results confirm the findings of previous studies that showed a positive association between the referee experience and the level of referees' self-efficacy [14,15,22], but not the one in the research of Dereceli on the self-efficacy of football referees [15] and on the study on US volleyball referees [4].…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Araştırmacılar ayrıca dörtlü likert sistemi yerine beşli derecelendirme sistemi kullanarak, ölçeğin geçerlik ve güvenirlik analizlerini gerçekleştirmişlerdir. Analizler sonucunda, ölçeğin Türk popülasyonunda kullanılabilir bir ölçek olduğu araştırmacılar tarafından belirtilmiş(Karaçam ve Pulur, 2017) ve ülkemizde bazı araştırmalarda kullanılmıştır(Adıgüzel, 2018;Dereceli, Ünlü, ve Erbaş, 2019; Eskiyecek ve ark., 2019;Karacam ve Adıguzel, 2019;Karaçam ve Pulur, 2019;Kılıç ve Öner, 2019;Koçak, 2019).…”
unclassified